KEDUDUKAN ADMINISTRASI NEGARA SEBAGAI MEDIATOR PENYELESAIAN SENGKETA HUBUNGAN INDUSTRIAL - Agus Iskandar (Universitas Bandar Lampung (UBL), 2019)
UU no. 17 Th. 2007 concerning the National Long Term Development Plan for 2005-2025mandates that harmonious industrial relations with proper protection, as well as therealization of industrial settlement processes that satisfy all parties, are characteristic of thedesired labor market. In connection with this, the purpose of this study is to examine andanalyze the position of state administration as a mediator in creating harmonious relations.The method used in this research is normative juridical approach. To analyze data and drawconclusions from the results of the study, a qualitative normative analysis method is used.The results showed that the position of State Administration as a mediator in creating aharmonious relationship is as a coach and executor of resolving industrial relations disputesoutside the court, in order to direct the disputing parties to deliberate so that they canproduce a wise agreement and can be carried out as efficiently as possible to the system ofnorms, systems of behavior, and value systems that are in accordance with Pancasila as theideology of the state. The government is expected to intensify the development of industrialrelations to the public, especially the workers and employers community, by furtherhighlighting complaints resolution institutions and making regular observations so thatindustrial relations disputes can be addressed early